Chromosome numbers of some Brazilian species of diplopods (Diplopoda, Arthropoda) - Fontanetti, Carmem Silvia [UNESP] (International Society of Cytology, 1998)
The present paper presents the chromosome numbers of five brazilian species of diplopods: Plusioporus setiger (2n = 10 and 2n= 10+ lB, the distinction of the sexual pair was not possible), Pseudonannolene ophiulus (2n=12, XY), Pseudonannolene halophila (2n=16, XY), Rhinocricus sp. (2n=28, XY) and Rhinocricus padbergi (2n=20, the distinction of the sexual pair was not possible).
Keywords: Chromosomes; Cytogenetics; Diplopods; Millipedes; Plusioporus setiger; Pseudonannolene halophila; Pseudonannolene ophiulus; Rhinocricus; Rhinocricus padbergi